La Camila de Camilo Henríquez o el dilema corneliano de la minoría criolla - Dardo Scavino (Cuadernos LIRICO)
Through the ethical dilemma between the loyalty to the blood family or to the political family, La Camila o la Patriota de Sud-América, written by the friar Camilo Henríquez, stages the contradictions of the Creole minority during the Americans revolutions.